2014
DOI: 10.1177/2047487314533084
|View full text |Cite
|
Sign up to set email alerts
|

Hypotestosteronemia is frequent in ST-elevation myocardial infarction patients and is associated with coronary microvascular obstruction

Abstract: Our study shows higher prevelence of hypotestosteronemia among STEMI patients as compared with SA patients and among STEMI patients with MVO as compared with those without, thus suggesting a possible role of T deficiency in coronary instability and MVO pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…18 However, several reports found that only free testosterone was significantly lower in men with coronary artery disease. 107 –110 It has also been shown that a low testosterone level was associated with atherosclerosis 111 and myocardial infarction 112 in men, supporting the previous findings that low levels of testosterone could increase the risk and contribute to a high prevalence of coronary artery disease in men. 22,110,113 116 In addition, the level of testosterone shows an inverse correlation with the severity of coronary artery stenosis.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…18 However, several reports found that only free testosterone was significantly lower in men with coronary artery disease. 107 –110 It has also been shown that a low testosterone level was associated with atherosclerosis 111 and myocardial infarction 112 in men, supporting the previous findings that low levels of testosterone could increase the risk and contribute to a high prevalence of coronary artery disease in men. 22,110,113 116 In addition, the level of testosterone shows an inverse correlation with the severity of coronary artery stenosis.…”
Section: Introductionsupporting
confidence: 61%
“…109 Men with MI 100 -Patients with STEMI and SA had low testosterone level -Hypotestosteronemia prevalence was higher among patients with STEMI compared with patients with SA -Hypotestosteronemia independently predicted both angio-MVO and ECG-MVO Testosterone deficiency may contribute to the development of coronary instability and MVO pathogenesis. 112 Men with CAD 111 -Plasma testosterone level was inversely correlated with the degree of coronary stenosis. -Higher blood level of TT was associated with the lower number of stenosis in the coronary arteries.…”
Section: Resultsmentioning
confidence: 98%
“…Critical illnesses can cause decreased testosterone levels; therefore, HBV-ACLF itself may contribute to lower TT. Previous studies have reported the high incidence of testosterone de ciency among critically ill patients with condition such as myocardial infarction and acute respiratory failure [19][20] . New evidence indicates that lipopolysaccharide, which promotes the development of ACLF [21] , may initiate in ammation and result in impaired Leydig cell function thus reduce testosterone production in men [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Niccoli et al examined the link between hypotestosteronemia and coronary microvascular obstruction (MVO) in patients with STEMI and revealed a higher prevalence of hypotestosteronemia in patients with STEMI compared to those with stable angina as well as in STEMI patients with MVO after PCI suggesting the potential effect of testosterone deficiency in the pathogenesis of MVO [ 25 ]. In their study, lower levels of testosterone in STEMI patients was associated with reduced success rate of PPCI as mentioned by lower post PCI TIMI flow.…”
Section: Discussionmentioning
confidence: 99%